Agricultural Literacy: A Framework For Communicating To The Public Sector - Martin J. Frick; Alan A. Kahler; W. Wade Miller (Journal of Applied Communications, 1991)
The purposes of this study were to refine a group definition of agricultural literacy, identify agricultural subject areas that fall within the framework of agricultural literacy, and identify those concepts about agriculture that every citizen should know.